Artikel Review: Pengaruh pH pada Pertumbuhan Bakteri Sesuai Syarat Mutu Obat Tradisional di Indonesia - Ivanny O. Y. Sinaga; Dwie Astrini; Raden B. Indradi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Traditional medicine comes from safe ingredients, namely, parts of plants. Based on BPOM No. 32 of 2019, several bacteria are required for the quality of traditional medicines in Indonesia, including Escherichia coli, Clostridia, Salmonella, and Shigella. An optimal pH medium is also needed in the microbial contamination test to produce optimal bacterial growth data. The method used is library search using electronic databases such as Google Scholar and Pubmed with the keywords